Public distribution system and food security: evidence from Barpeta district, Assam. Issue 4 (18th May 2020) - Maity, Shrabanti
ABSTRACT: This article investigates the role of the public distribution system (PDS) in ensuring food security in marginal areas of India such as Barpeta district in Assam, with special references to the char and non- char areas. The study used Dietary Diversity Score, Food Consumption Score and a self-developed Food Security Index to identify the food security status of the area. The role of PDS was investigated using propensity score matching. The study established that the PDS ensures food security in terms of all the indicators, and makes PDS beneficiaries more food-secure than non-participants even for char areas. Therefore, PDS can be an important instrument to ensure food security in a marginalised area.